Pengembangan Modul Bimbingan Karier Berbasis Pendekatan Karakter Kinerja Di SMA - Samy Purnamy Drachman; Rufi'i; Muhammad Muhyi (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2020)
The career development program aimed to guide students to secure employment. This study contributed to the discussion by developing a career development module with character development as guidance of students’ decision making. Sixty students participated in this study, analyzed with a quantitative descriptive method. This study revealed that the design validation was 92%, with 4,6, as good. Content validation was 96% or the average of 4,8 (good). Instrument Validation was also good. Partner validation was 92%, or 4,6 (good). After designing, this study applied the development test. The result revealed the test of a small group to be 88,5%, middle group to be 91,8%, and a big group to be 93,1%. This study concluded the career development module was good for field application and offered precious information to the school counselor, counseling supervisor, and the counselor herself.